Chapter 3 Autophony: Listening to your Eyes Move - Harris, Anna (Mattering Press, 2017)
I observed many instances of self-percussion during my fieldwork researching how listening to sounds is learned, taught and practiced in a Melbourne medical school and it's connected teaching hospital. The students were sounding out their own bodies; practicing the technique while also feeling "dull" or "resonant" on their own body. This knowledge was then to be applied during their examination of patients, where dullness or resonance in the "wrong" place or in uneven distribution, may indicate disease. Tom Rice (2013) also observed similar acts of self-listening in a London hospital, in the form of auto-auscultation. The first sounds a medical student listens to, Rice found, when they buy their first stethoscope, are often their own. What does it mean to use your body as a case for others? Medical students (and indeed many other practitioners of the body) do this all the time. It is a common way of learning new bodily skills and bodily knowledge.